Pattern of surgical emergencies during COVID-19 lockdown in a tertiary care centre - Verma, Surender; Verma, Anjali; Garg, Pradeep; Godara, Rajesh; Sirohi, Vivek; Garg, Neha; Pal, Vijay (International Surgery Journal, 2020)
Background: COVID-19 is a novel pandemic affecting almost all countries of the world. The containment measures in form of lockdown taken to prevent its spread has impacted pattern and volume of surgical emergencies. As emergency admissions form a major bulk of total surgical admissions hence this study was planned to look for the impact of lockdown on the spectrum of surgical emergencies in a tertiary care hospital. Methods: A descriptive register based study was done by collecting data of surgical emergencies in three phases – pre lockdown, lockdown and lockdown with relaxations. Data regarding surgical admissions which includes trauma as well as non-trauma emergencies during various phases was collected and analysed. Results: Total number of surgical emergencies decreased by 55.6% during lockdown when compared with pre-lockdown phase. In lockdown phase with relaxations, total admissions increased by 35.2% over lockdown phase however they was overall decrease by 19.4% than pre-lockdown phase. Physical assault was most common cause of trauma admissions in both lockdown (48.2%) as well as relaxation phases (57.1%) whereas RSA was the most common cause in pre-lockdown phase (50.5%). Conclusions: As there was significant decrease in surgical emergencies particularly road side accidents during both lockdown and relaxation phases, hence we conclude that maximum emergencies can be avoided which ultimately decrease the burden on existing health care system. However lockdown has adversely affected economy of country and public comfort i.e. travel restrictions, jobs, recreation etc. Moreover, rise in cases of physical assaults also warrants urgent attention in the community.